Strategic Profiles of the International Dimension in Universities in Uganda - and Florence Nakamanya, Ronald Bisaso (International Journal of African Higher Education, 2020)
This article is based on a study that explored the nature of and variations in strategic profiles of internationalisation in universities in Uganda. Six universities, comprising of three public and three private chartered universities with different histories and philosophies were selected for the study. Profiles of the international dimension were ascertained through a review and analysis of national and institutional strategic plans and reports. The findings highlight six profiles of internationalisation, namely, vision and mission, shared/core value, student enrolment, staff and student exchange, partnerships and collaborations, and the management structure. It is imperative that universities integrate internationalisation as an ethos that is systematically mainstreamed in all activities, produce knowledge relevant to local and international audiences, and improve the management structure by deploying managerial capacity that corresponds to the strategic period. The article recommends that further research should be conducted on profiles of the international dimension.